Tunneling Spintronics across MgO Driven by Double Oxygen Vacancies. (10th May 2017) - Taudul, Beata; Monteblanco, Elmer Nahuel; Halisdemir, Ufuk; Lacour, Daniel; Schleicher, Filip; Montaigne, François; Beaurepaire, Eric; Boukari, Samy; Hehn, Michel; Alouani, Mébarek; Bowen, Martin
Abstract : Tunneling spintronic devices are foreseen to play an important role in emerging technologies, from data read‐out and storage to processing, including neuromorphic computing. A counterintuitive suspicion is that double oxygen vacancies within the commonly used MgO barrier underscore the high spintronic performance. Here, how the peculiar electronic properties of these nanoscale objects experimentally enhance spintronic performance is demonstrated. The vacancy's ground state near the Fermi level theoretically promotes enhanced transmission across the barrier of electrons with the Δ1 electronic symmetry that drives high spintronic performance. Annealing the MgO barrier experimentally increases the ratio of double to single oxygen vacancies. This promotes a lower Δ1 barrier height, reduces the Δ5 transmission, and enhances spintronic performance, in agreement with theory. This novel nanoscale paradigm of tunneling spintronics should affect all research that utilizes this low barrier height (e.g., spin transfer torque), help establish an ultimate limit on laterally downscaling these devices, and promote new nanoscale quantum computing concepts. Abstract : Theory and experiments show how double oxygen vacancies drive the spintronic performance of MgO‐based magnetic tunnel junctions. The double oxygen vacancy favorably alters tunneling transmission, its density can be enhanced experimentally, and its spatial extent defines an ultimate limit for device lateral downscaling. This paradigm of vacancy‐driven MgO spintronics shall impact spin transfer torque and quantum computing research, toward oxide electronics.